Material Process in Electrical Products Catalogues: A Systemic Functional Analysis - Nugraha, Hendra; Selinna (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This study aims to analyze the type of material process, focusing on the Electrical field, specifically using electrical product catalogue. Therefore, this study employed the Systemic Functional Linguistic (SFL) framework to analyze the descriptive qualitative data obtained, a total of 50 data of clauses were collected from two electrical products catalogues. The data were categorized and analyzed in a table. The result of this research showed that there are 42% of Creative Transitive clause, 36% of Creative Intransitive clause, 20% of Transformative Transitive clause, and 2% of Transformative Intransitive clause.